STRUCTURAL TYPOLOGY OF HYDRONYMS AND AN ANALYSIS OF MORPHEMIC COMPOSITION IN UZBEK AND ENGLISH RIVERINE TOPONYMS - Sanginova Umeda Umbarovna; Zafarova Parvina Rustam qizi; Murodova Sevara (Western European Studies, 2026)
This article explores the general concept of hydronyms, their fundamental definitions, and the reasons why they should be studied. It provides a comparative analysis of hydronyms in Uzbek and English, examining their ancient origins, morphological structures, and their role within the theories of morphology and toponymy. Particular attention is given to the historical roots and structural features of the most frequently occurring suffixes in both Uzbek and English hydronyms.
Keywords: river; Uzbek; English; linguistics